2009
DOI: 10.1038/onc.2009.355
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of premature senescence requires JNK regulation of Bcl-2 and reactive oxygen species

Abstract: Premature senescence is considered as a cellular defense mechanism to prevent tumorigenesis. Although recent evidences show that c-Jun N-terminal kinase (JNK) is involved in the senescence process, the mechanism for this regulation is not fully understood. Here, we examined the role of JNK in premature senescence of tumor cells. Treatment of cells with the JNK-specific inhibitor SP600125 caused phenotypical changes of senescence and triggered a rapid increase in mitochondrial reactive oxygen species (ROS) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 65 publications
11
63
0
Order By: Relevance
“…1B and D), suggesting that the JNK activity is required for the proliferation of A549 cells irrespective of the culture condition, at least in vitro. These results were essentially consistent with those of previous studies that demonstrated the essential role of JNK in the in vitro growth of NSCLC cells using NSCLC cell lines other than A549 (16)(17)(18).…”
Section: Rapid and Potent Inhibition Of A549 Cell Proliferation By Jnsupporting
confidence: 82%
See 1 more Smart Citation
“…1B and D), suggesting that the JNK activity is required for the proliferation of A549 cells irrespective of the culture condition, at least in vitro. These results were essentially consistent with those of previous studies that demonstrated the essential role of JNK in the in vitro growth of NSCLC cells using NSCLC cell lines other than A549 (16)(17)(18).…”
Section: Rapid and Potent Inhibition Of A549 Cell Proliferation By Jnsupporting
confidence: 82%
“…Similarly to glioblastomas (12)(13)(14)(15), aberrant activation of JNK has been observed frequently in NSCLC tumors (16,17), and a number of studies do provide evidence Specific role of JNK in the maintenance of the tumor-initiating capacity of A549 human non-small cell lung cancer cells supporting the idea that JNK has a positive role in promoting the growth of NSCLC tumors (16)(17)(18). Nevertheless, evidence…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, because Sab is also a substrate of JNK (5, 6), one can speculate that JNK mitochondrial translocation is dependent upon the ability of JNK to phosphorylate Sab. JNK can then use established Bcl-2 proteins and BH3 proteins as substrates (2)(3)(4) or it can initiate new signaling cascades that result in the inhibition of respiratory Complex I. After 60 min activated JNK leaves the mitochondrial membrane (Step 3) after altering mitochondrial physiology (T), and cell death or survival functions (Step 4) are initiated.…”
Section: Discussionmentioning
confidence: 99%
“…We also previously reported that IR induces premature senescence in breast, colon, and lung carcinoma, and in tumor tissue of xenografted mice. 20,39 Therefore, understanding premature senescence mechanisms could provide helpful information for improving the efficacy of RT.…”
Section: Discussionmentioning
confidence: 99%